A Portuguese East Indiaman from the 1502–1503 Fleet of Vasco da Gama off Al Hallaniyah Island, Oman: an interim report. (1st September 2016) - Mearns, David L.; Parham, David; Frohlich, Bruno
Abstract : Two Portuguese naus from Vasco da Gama's second voyage to India, left behind to disrupt maritime trade between India and the Red Sea, were wrecked in May 1503 off the north‐eastern coast of Al Hallaniyah Island, Oman. The ships, Esmeralda and São Pedro, had been commanded by da Gama's maternal uncles, Vicente and Brás Sodré, respectively. A detailed study and scientific analysis of an artefact assemblage recovered during archaeological excavations conducted in Al Hallaniyah in 2013 and 2014 confirms the location of an early 16th‐century Portuguese wreck‐site, initially discovered in 1998. Esmeralda is proposed as the probable source of the remaining, un‐salved wreckage. Abstract : في مايو 1503م تحطمت سفينتان من سفن الناوس البرتغالية من أسطول فاسكو دي جاما من رحلته الثانية للهند على الساحل الشمالي الشرقي لجزيرة الحلانيات في سلطنة عمان ،واللتان تركتا لتعطيل التجارة البحرية في المنطقة بين الهند والبحر الأحمر. السفينتان إزمارالدا و ساو بيدرو كانتا تحت قيادة كلاً من فيسنتي و براس صودري على التوالي أخوال فاسكو دي جاما. تأتي هذه الدراسة المفصلة والتحاليل العلمية للقطع الأثرية التي تم إكتشافها من خلال الحفريات الأثرية التي أجريت في جزيرة الحلانيات بين عامي 2013 و 2014 م لتؤكد أن الموقع يعتبر من أوائل مواقع حطام السفن البرتغالية للفترة من أوائل القرن السادس عشر، والذي قد تم إكتشافه بدايةً عام 1998م. تفضي الدراسة إلى أن بقايا الحطام المكتشفة قد تعود في المقام الأول إلى السفينة إزمارالدا . Abstract : Duas naus portuguesas pertencentes à armada que Vasco da Gama liderou na sua segunda viagem à India ficaram no Índico para perturbar o comércio entre a India e o Mar Vermelho, naufragando em Maio de 1503 junto à costa nordeste da ilha Al Hallaniyah, no Omã. Aqueles navios, Esmeralda e São Pedro, eram liderados pelos tios maternos de Vasco da Gama, Vicente e Brás Sodré, respetivamente. O sítio foi descoberto em 1998 e escavado em 2013 e 2014. O estudo detalhado e análises científicas da coleção de artefactos recuperada durante a escavação arqueológica confirmam a localização do naufrágio de uma embarcação portuguesa do século XVI. Propõem‐se que os vestígios encontrados pertençam à carga não salvada da Esmeralda.